RURAL RESIDENTS PERCEPTIONS ON ECONOMIC IMPACTS OF CULTURAL AND PROMOTIONAL ASPECTS OF TOURISM - Vujko, Aleksandra; Zečević Stanojević, Olgica; Zečević, Leposava; Nedeljković, Dragan; Zečević, Milija (Economics of Agriculture, 2021)
This study investigates residents attitudes to tourism impacts (marketing, culture etc.) on Fruška Gora Mountain (Serbia), within the larger framework of economic impacts. The correspondence analysis of the perception of local residents showed that residents have a generally positive attitude to wards the development of tourism considering its economic aspects, and then the desk study show edjustification of positive attitudes, thus confirming the main hypothesis. Accord ing to the analysis of the opinions of the local residents, it was found that the local residents positively perceived economic impact of tourism in two aspects: through increase in number of employees (employment and self-employment) as well as through the development of the community. The development of tourism in any destination in evitably leads to an increase of domestic and foreign investment, which then leads to the construction of infrastructure and suprastructure facilities, the introduction of various tourist taxis, and if it is possible, as it is the case with Fruška Gora Mountain, it can lead to a success-ful cross-border cooperation.